Space Syntax for Evaluating Attractivity and Visit Frequency: A Comparative Study of Two Public Squares of Downtown Setif (Algeria) - Tedjari, Abdelmalek Farouk; Abbaoui, Messaoud (Engineering, Technology & Applied Science Research, 2023)
The current study uses the Space Syntax innovative method for determining the causes of the attractivity and visit frequency gap between two open public spaces of downtown Setif (Algeria): Sahat El Istiklal square and Masjid Ibn Badis square. A design drawn from a map coming from the National Institute of Cartography and Teledetection (Algeria) is chosen for the configurative analysis carried out by Space Syntax through the DepthMap software. Visibility Graph Analysis (VGA) superimposed with the pedestrian real flow permits the visual integration of the analysis of each square. The analysis revealed relevant gaps in the syntactic measure values obtained for each square emphasizing their positive aspects and specific problems. Space Syntax allows the extension of the initial discussion about public squares in urban environments and to work out causality relationships between spatial configuration and human behavior.